2013
DOI: 10.1152/ajpheart.00637.2012
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between A2A adenosine receptors, hydrogen peroxide, and KATP channels in coronary reactive hyperemia

Abstract: Myocardial metabolites such as adenosine mediate reactive hyperemia, in part, by activating ATP-dependent K(+) (K(ATP)) channels in coronary smooth muscle. In this study, we investigated the role of adenosine A(2A) and A(2B) receptors and their signaling mechanisms in reactive hyperemia. We hypothesized that coronary reactive hyperemia involves A(2A) receptors, hydrogen peroxide (H(2)O(2)), and KATP channels. We used A(2A) and A(2B) knockout (KO) and A(2A/2B) double KO (DKO) mouse hearts for Langendorff experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 53 publications
4
51
0
Order By: Relevance
“…[17][18][19] When activated, adenylate cyclase leads to the production and accumulation of cAMP that activates protein kinase A, which ultimately produces smooth muscle cell hyperpolarization and relaxation, particularly through the activation of intermediate-conductance K Ca channels. [20][21][22] Therefore, adenosine-induced peripheral and coronary dilatation is mainly mediated through the activation of A 2A and A 2B receptors. However, on the other side, it has been consistently observed that the inhibition of adenylate cyclase (mediated by the A 1 and A 3 receptors) leads to vasoconstriction.…”
Section: Coronary and Systemic Effects Of Adenosine Infusionmentioning
confidence: 99%
“…[17][18][19] When activated, adenylate cyclase leads to the production and accumulation of cAMP that activates protein kinase A, which ultimately produces smooth muscle cell hyperpolarization and relaxation, particularly through the activation of intermediate-conductance K Ca channels. [20][21][22] Therefore, adenosine-induced peripheral and coronary dilatation is mainly mediated through the activation of A 2A and A 2B receptors. However, on the other side, it has been consistently observed that the inhibition of adenylate cyclase (mediated by the A 1 and A 3 receptors) leads to vasoconstriction.…”
Section: Coronary and Systemic Effects Of Adenosine Infusionmentioning
confidence: 99%
“…Hearts with persistent arrhythmias were excluded from the study. As a positive control, a 15-s flow occlusion resulted in a twofold increase in coronary flow over baseline [19,38], indicating that bufferperfused hearts have minimum hypoxia and coronary vessels have the capacity to further dilate.…”
Section: Animalsmentioning
confidence: 99%
“…Furthermore, pertinent to this effect, it may also be possible that adenosine-generated ROS is involved in mediating reactive or functional hyperemia, despite the role of adenosine in functional hyperemia remaining controversial [19]. Indeed, the involvement of adenosine in either reactive or functional hyperemia has been shown to be mediated by endogenously released vasodilators, including NO, prostacyclin, and endothelium-derived hyperpolarizing factor [38,40,63,64]. The influence and interaction of these vasoactive factors in generation of ROS by A 2A AR in the coronary circulation remain unclear.…”
Section: Adenosine-induced Increase In Coronary Flow Is Mediated In Pmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the complexity of the combined intrinsic (e.g., myogenic, shear-mediated, metabolic, and endothelium-originated mediators) with extrinsic (neural hormonal regulatory mechanism) blood flow control mechanisms make whole animal study a nonoptimal model for the mechanistic exploration in local metabolic coronary blood flow regulation. Therefore, there is a need to reexamine the functional role of adenosine in coronary metabolic hyperemia using combined AR knockout (KO) mice with traditional pharmacological agents in isolated Langendorff-perfused hearts.Increasing evidence suggests that H 2 O 2 , an endogenous metabolite, acts as an important mediator responsible for metabolic coronary vasodilation (37,42,53,54). We (42, 57) have previously demonstrated that A 2A AR-mediated H 2 O 2 production opens ATP-sensitive K ϩ (K ATP ) channels in coronary smooth muscle cells, contributing to the coronary ischemic vasodilation (42, 57).…”
mentioning
confidence: 99%